What is a scientific experiment?: The impact of a professional development course on teachers’ ability to design an inquiry-based science curriculum - Pérez, María del Carmen B. (2016)
Designing inquiry-based science lessons can be a challenge for secondary school teachers. In this study we evaluated the development of in-service teachers’ lesson plans as they took part in a 10-month professional development course in Peru which engaged teachers in the design of inquiry-based lessons. At the beginning, most teachers designed either confirmatory or structured inquiry activities. As the course progressed, however, they started designing guided and open inquiry lesson plans. We found four factors that accounted for this change: re-evaluating the need for lab materials, revising their views on the nature of science, engaging in guided and open inquiry activities themselves, and trying out inquiry-based lessons with their own students. Our results point to the importance of engaging teachers in prolonged and varied opportunities for inquiry as part of teacher education programs in order to achieve the challenge of changing teachers’ views and practices in science education.